The Effect Of Blended Learning Implementation On Learning Motivation And Learning Outcomes Of Nursing Students During The Covid-19 Pandemic - Nurlaela Amin A.; Amirullah; Tenriola Andi; Samsidar (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2023)
The Corona Virus Disease pandemic has had an impact on changes in the order of human life in various sectors throughout the world, including the education sector. One type of learning using internet technology (e-learning) that has been effectively used in higher education is blended learning. The application of Blended learning motivates students to better understand the material and be more active in participating in learning, so as to improve student learning outcomes. The research objective is to identify and explore the implementation of blended learning on learning motivation and learning outcomes of nursing students during a pandemic. The research design used was Mix Methods with a sequential explanatory approach, the sample in the quantitative study was 76 people and the qualitative research was 8 people with the sampling technique being simple random sampling. The results of the study with the Chi square test obtained a value of p = 0.019 (<0.05), which means that there is an influence between learning methods and learning outcomes, and qualitative research identified four themes, namely: 1) Internal motivation, 2) External motivation, 3) Supporting factors, and 4) inhibiting factors. There is an effect of the application of blended learning on student learning outcomes during the pandemic. Learning motivation is not only influenced by internal and external motivation, but comes from supporting factors and inhibiting factors. It is hoped that further research can dig deeper into other learning methods related to student motivation and learning outcomes. Keywords: Blended Learning, Learning Motivation, Learning Outcomes